A High-Throughput Fast Chromatography-Tandem Mass Spectrometry-Based Method for Deoxynivalenol Quantification in Wheat Grain - Lipu Wang; Deborah Michel; Wentao Zhang; Anas El-Aneed; Pierre R. Fobert; Yuefeng Ruan; Samia Berraies; Richard Cuthbert; Hadley R. Kutcher (PhytoFrontiers, 2022)
Fusarium head blight (FHB), caused by Fusarium spp., is a destructive disease of cereal grains. Apart from grain yield loss, a major quality concern is contamination with Fusarium-produced mycotoxins, specifically deoxynivalenol (DON). Mycotoxins accumulate in the grain, making it unfit for consumption by humans and animals. Breeding cultivars with high disease resistance and low mycotoxin contamination is a priority for wheat breeders. However, DON measurement in breeding programs is expensive and time consuming due to the lack of efficient quantification methods. In this study, we established a simple fast chromatography-tandem mass spectrometry method, which employed a one-step acetonitrile extraction protocol with a short guard column to reduce complexity, cost, and analysis time. To ensure robustness and reproducibility, the method was validated according to the U.S. Food and Drug Administration Guidance for Bioanalytical Method Validation. Furthermore, the method was applied for determination of DON in 102 wheat grain samples. Obtained results highly correlated with the conventional immunological method for all tested samples. With its ease of use, rapid sample analysis, and high sensitivity and accuracy, the method could be integrated into current FHB breeding programs to increase breeding efficiency and accelerate screening progress to identify germplasm with increased resistance to DON accumulation. [Figure: see text] Copyright © 2022 The Author(s). This is an open access article distributed under the CC BY 4.0 International license.